The use of non-pharmacological interventions for the comfort of patients in palliative care: a scoping review protocol - Coelho, Adriana (2020)
The objective of this scoping review is to examine and map the non-pharmacological interventions implemented and evaluated to provide comfort in palliative care. More specifically, the review will focus on the following questions: 1. What non-pharmacological interventions have been implemented and evaluated to provide comfort in patients with incurable and advanced diseases? 2. What are the characteristics (duration, dose and frequency) of these interventions? 3. In what contexts (home care, palliative care unit or hospice) are the non-pharmacological interventions implemented and evaluated? 4. In which populations (cancer and non-cancer patients) are the non-pharmacological interventions implemented and evaluated?